PENGARUH PEMBERIAN KOMPOS BRANGKASAN TANAMAN JAGUNGTERHADAPPERTUMBUHAN BIBIT KARET (Hevea brasiliensis Muell. Arg) - Rudi Fernando; Tengku Nurhidayah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research aims to determine the effect of giving brangkasan compost corn plant and get the best dose to the growth of rubber seeds. This research has been conducted in the Experimental Garden of Agriculture Faculty University of Riau from April until August 2018. The research was conducted experimentally by using Completely Randomized Design (CRD), with six treatments and three replications. Treatments has given consist of brangkasan compost plant corn with dose of 0 g, 40 g, 80 g, 120 g, 160 g and 200 g per 8 kg soil. Parameter observed were increasing of heigh seeds, increasing stem cicumfrence, increasing number of leaves, length of the longest leaves, and width of the most wide leaves. The data obtained were analyzed statistically using analysis of variance with Duncan New Multiple Range Test (DNMRT) at 5%. Giving brangkasan compost corn plant with dose 200 g per 8 kg soil is the better choice to improve the increasing of heigh seeds, increasing stem cicumfrence, increasing number of leaves, length of the longest leaves, and width of the most wide leaves. Keywords :Hevea brasiliensis, brangkasan compost corn plant